InsurTech Aggregator: Menuju Masa Depan Industri Asuransi Digital di Indonesia - Trisna Taufik Darmawansyah; Sanawi Sanawi; Muhamad Fadli Azim; Santi Angraini; Muhamad Turmudi (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
The purpose of this study is to conduct a SWOT analysis on InsurTech Aggregator in identifying the strengths, weaknesses, opportunities, and threats faced in the development of online insurance business. Qualitative descriptive methodology is used to gain a deep understanding of InsurTech Aggregator in Indonesia and the insurance products offered. Meanwhile, SWOT analysis will help identify the strengths and weaknesses of the InsurTech Aggregator company, as well as the opportunities and threats that exist in the insurance industry environment. The results of the study obtained an IFAS value of 3.00 and an EFAS value of 2.59. The implication of this study is a strategy for insurance companies to implement the S-O strategy, the steps that can be taken are to utilize the company's internal strengths to take advantage of existing external opportunities. Utilizing the advantages of InsurTech which are easily accessible and practical and the ability to compare policies to develop omnichannel services so as to increase sales opportunities and customer trust. Using an easy and effective claims process to build a strong corporate image, and integrating complex insurance products with services that are easier for prospective customers to understand.